THE POWDER OF Co64Nb30B6 OBTAINED BY MECHANICAL ALLOYING - Luciano Nascimento; Ítallo Campos Gonçalves de Morais; Adriano Lima da Silva; João Baptista da Costa Agra de Melo; Danyelle Garcia Guedes; Lincoln Rodrigues Sampaio de Araújo; Suédina Maria de Lima Silva; Ana Cristina Figueiredo de Melo Costa (Química Nova, 2024)
This work aims to synthesize the alloy Co64Nb30B6 through mechanical alloying using a planetary ball mill. A disc rotation per minute and a ball/powder weight ratio of 300 rpm and 10:1 were used, with a milled time of 10 h, respectively. The characterization of the Co64Nb30B6 alloy was performed by X-ray diffraction (XRD), examined by scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDS), thermoanalytical techniques (TGA/DTA), vibrating sample magnetometer (VSM) and confirmed by Braunauer, Emmet e Teller (BET) method type IV isotherms with a hysteresis loop for mesoporous materials. The results indicated that the evolution of the amorphous phase in the Co64Nb30B6 composition through the mechanical alloying process exhibited good soft magnetic properties with the addition of the metalloid element B and its excellent unique ferromagnetic properties. Through thermoanalytical analysis (TGA/DTA), it was shown that at higher temperatures, Co and Nb ions are oxidized by the environment and, therefore, the mass can be slightly increased to 14.9% and a probable contribution of boron in evolution stability thermal and magnetic in the amorphous phase, respectively. This suggests that the newly developed high-performance amorphous alloy Co64Nb30B6 has great application potential.